Parenting as an inhibitor of gender disparities in alcohol use: the case of early adolescents in China - Bo, Ai; Jaccard, James (BMC public health, 2020)
Background Gender differences in alcohol use are more substantial among early adolescents in China than in the United States, presumably because of more permissive drinking norms for boys than girls in Chinese culture. This study tested a theory that gender differences in early experimentation with alcohol can be reduced through general parenting practices. Whereas traditional research has identified mediators of gender differences in alcohol use, the current research isolated moderators of gender differences and developed their implications for prevention programs. Methods The study analyzed the data from the China Global School-Based Student Health Survey ( n = 8805 middle school students in four cities). Youth completed anonymous surveys in classroom settings. The study examined interaction effects between gender and parenting variables using multiple regression with robust standard errors. Results Early adolescent boys exhibited higher levels of drinking than girls for all drinking outcomes. The gender differences in drinking were negatively associated with the level of perceived parental monitoring, parental involvement in adolescent school performance, and parental empathy in a nonlinear way. Conclusions Results suggested that early adolescents’ perceptions of general parenting practice nonlinearly moderated gender disparities in alcohol use.